The Relationship of Knowledge and Husband's Support With The Use of Injective Contraceptions - Lanita, Usi; Sarah Soldia Oktavia; Puspita Sari; Kasyani Kasyani; Sri Astuti Siregar (The International Science of Health Journal, 2023)
The family planning (KB) program is a government effort to prevent risky pregnancies due to the 4Ts (too young, too old, too close, and too frequent). One of the birth control methods most widely used by women of childbearing age (WUS) is injectable birth control. The research aims to determine the relationship between a husband's knowledge and support and the use of injectable contraceptives in women of childbearing age. Method: quantitative research using a cross-sectional design with a cluster random sampling technique. Data were collected using a questionnaire, and analysis was carried out using the Chi-Square statistical test. Results: There is a relationship between knowledge (p-value 0.046) and husband's support (0.001) with the use of injectable contraceptives in women of childbearing age (WUS) in the Tanjung Pinang Health Center Working Area, Jambi. Conclusion: There is a relationship between a husband's knowledge and support and the use of injectable contraceptives in WUS, so it is hoped that health workers will routinely provide outreach regarding the use and benefits of injectable contraceptives to couples of childbearing age (PUS).